OCEAN BIG DATA SEBAGAI LANGKAH PENCEGAHAN KEGIATAN ILLEGAL FISHING - Ranti Saripah; Rani Mariana (Jurnal Penelitian Hukum Galunggung, 2026)
Indonesia is a maritime and archipelagic country and is recognized as the largest archipelagic state in the world. This is reflected in its extensive marine areas, comprising approximately 290,000 km² of territorial waters; 3,110,000 km² of internal and archipelagic waters; 2,800,000 km² of continental shelf waters; and 3,000,000 km² of Indonesia’s Exclusive Economic Zone (EEZ). Based on research conducted by the National Fish Stock Assessment Commission (Komisi Nasional Pengkajian Stok Ikan/KOMNASJISKAN), fishery resources experienced a decline in 2025 compared to 2023, one of the contributing factors being illegal fishing activities. Illegal fishing has caused significant financial losses to the state by substantially reducing productivity and fish catches, while also threatening Indonesia’s marine fishery resources. This study employs a normative legal research method using a statutory approach, examining various policies for addressing illegal fishing, including law enforcement and preventive measures. Based on an analysis of several policies for addressing illegal fishing, the use of Ocean Big Data is considered a more effective and efficient approach with significant potential to minimize illegal fishing activities through preventive measures. By adopting this comprehensive approach, Indonesia can strengthen the effectiveness of sustainable fisheries management, ensure the welfare of fishers, and safeguard the long-term sustainability of the national fisheries industry.